Brand Trust As A Moderating Variable Of The Influence Of Instagram Vloggers On Food Branding - Bagus Yunianto Wibowo; Nanang Adie Setyawan; Jati Nugroho; Misbakhul Arrezqi; Eva Purnamasari; Irawan Malebra (UNIVED Press, 2026)
This research is quantitative with an explanatory approach, which utilizes primary source research to validate existing hypotheses . The data used in this study are primary data obtained from 250 Instagram users. The data in this study were analyzed using the Smart PLS 4.0 analysis tool. The result in this article show In this study, there are two hypotheses used. The hypothesis in this study is that the Instagram Vlogger variable can have a positive relationship direction and a significant influence on Food Branding. To find out the results can be seen in the first row of the third table. The first row of the third table in this study shows that the Instagram Vloggers variable can have a positive relationship direction and a significant influence on Food Branding because the P-Values are positive and below the 0.05 significance level, namely 0.000. The results mentioned by the researcher in the previous row are in line with a number of previous studies as follows (Hansvirgo et al. 2023); (Liling et al. 2022) & (Novindina Ayutiani 2022). These results mean that the increasing number of Instagram Vloggers about a product can make the product more known to the public and ultimately can increase the Food Branding of a product. The next hypothesis can be interpreted that the Brand Trust variable can also strengthen the influence of the Instagram Vloggers variable on Food Branding because the P-Values also tend to be positive and are also far below the 0.05 significance level, namely 0.000. More significant than direct testing. Based on this, the first and second hypotheses in this study can be accepted and proven.